Conservation Subdivision: Post-Construction Phase—Creating Signs to Educate Residents - Mark Hosteller (EDIS)
Installing educational signs is one way to increase awareness and participation in conservation activities. This 6-page fact sheet explains how to create educational signs and install them in residential neighborhoods as a way to inform residents about biodiversity conservation. The fact sheet, one of the UF/IFAS Conservation Subdivision series, explains how to design effective signs, how to manage a series of signs to keep the information fresh, and how to maintain the signs to ensure that residents and visitors to the community continue to benefit and maintain their homes, yards, and neighborhoods sustainably for years to come. Written by Mark Hostetler and published by the Department of Wildlife Ecology and Conservation, January 2016.